Simultaneous determination of arsenic (Ⅲ) and arsenic (Ⅴ) in polluted Sg. Riu, Perak water samples - Aljaffry, Alradhiatul Zulaikha Mohd (2020)
Contamination of the environment with arsenic (As) from both natural sources and anthropogenic activities has occurred in many parts of the world and also has been recognised as a global problem. Although there is no specific legislation for As species values but the researchers found that inorganic arsenic compounds are far more toxic and harmful than the organic ones. As contamination in Sungai Rui, Perak is widespread due to the mining location near the river. Objective of this research is to determine the concentration of inorganic As in polluted Sungai Rui, Perak sample. Therefore, anodic stripping voltammetry (ASV) method is preferred for As analysis mainly owning to its high selectivity and sensitivity. The highest concentration of As(Ⅴ) was noticeable in STA 10 (8.420±0.408) μg/L and the lowest was in water sample labelled STA 22 (3.323±0.385) μg/L. Most of the concentration of As(V) detected in between 3-7 μg/L while for As(Ⅲ) could not be established due to unsuitable condition. Thus, further study need to be done to achieve suitable method for simultaneous detection of As(Ⅲ) and As(Ⅴ).